The Voice of Dwellers - Developin a place brand by listening to the residents - Hakala Ulla (Emerald, 2022)
Purpose – Listening to the customers has long been a key phrase and success element in product branding.
This paper aims to highlight the importance of listening to residents during the branding of a place. The
study explores ways of listening to residents to ensure they are heard and also discusses the challenges and
benefits related to place branding flowing from having residents participate in decision-making processes.
Design/methodology/approach – Listening to residents and offering opportunities to participate requires
place branders to fully attend to, comprehend and respond to residents’ comments, requests, ideas and feedback. This study reports on how two Nordic cities – Turku and Helsinki – listen to their residents. The data used comprise face-to-face interviews, telephone and e-mail conversations and documentary material.
Findings – Residents should not be considered as one homogeneous target; participation options and channels should be adapted to the demographics and geographic issues of the different regions and resident groups.
Research limitations/implications – The role of residents and the importance of listening are crucial
features in the emerging concept of inclusive place branding (Kavaratzis et al., 2017); its future conceptual
development could benefit fromthe case examples at hand.
Practical implications – City authorities should listen to residents and provide them with opportunities
to actively contribute to decision-making. Other cities could learn from the examples introduced in the paper.
Originality/value – This paper documents two Nordic examples of cities putting into practice a policy of
listening to the residents, a previously neglected research area.
Keywords Stakeholders, Participation, Residents, Listening, City governance,
Inclusive place branding
Paper type Research paper